Social robots as eating companions - Niewiadomski, Radoslaw; Bruijnes, Merijn; Huisman, Gijs; Gallagher, Conor Patrick; Mancini, Maurizio (Frontiers in Computer Science, 2022)
Previous research shows that eating together (i.e., commensality) impacts food choice, time spent eating, and enjoyment. Conversely, eating alone is considered a possible cause of unhappiness. In this paper, we conceptually explore how interactive technology might allow for the creation of artificial commensal companions: embodied agents providing company to humans during meals (e.g., a person living in isolation due to health reasons). We operationalize this with the design of our commensal companion: a system based on the MyKeepon robot, paired with a Kinect sensor, able to track the human commensal’s activity (i.e., food picking and intake) and able to perform predefined nonverbal behavior in response. In this preliminary study with 10 participants, we investigate whether this autonomous social robot-based system can positively establish an interaction that humans perceive and whether it can influence their food choices. In this study, the participants are asked to taste some chocolates with and without the presence of an artificial commensal companion. The participants are made to believe that the study targets the food experience, whilst the presence of a robot is accidental. Next, we analyze their food choices and feedback regarding the role and social presence of the artificial commensal during the task performance. We conclude the paper by discussing the lessons we learned about the first interactions we observed between a human and a social robot in a commensality setting and by proposing future steps and more complex applications for this novel kind of technology.